'Los hòmens no són perfets': revelacions dels processos de fiscalització institucional. - CAPDEFERRO, JOSEP; SAN MIGUEL, ADRIÀ (Scripta, 2019)
In early modern Catalonia, every three years a powerful provincial representative institution called Diputació del General or Generalitat was subject to a strict accountability procedure which lasted nine months. Many records from these procedures provide us with priceless data about the fiscal, financial and political regular functions of the institution. They also inform us that some officials better cared about themselves than about the organism they were supposed to work for in unexpected ways such as using public slaves for private purposes. Through these records, especially testimonies at trial, we perceive that common people understood quite well what was the attitude that public officers were socially required to keep towards citizens. Arrogant behaviours were thus reprobated, such as other sorts of abuse of power.